Focal Therapy: A New Paradigm for the Treatment of Prostate Cancer - Tareen, Basir (MedReviews, LLC, 2009)
Focal therapy has been proposed in recent years as a means of bridging the gap between radical prostatectomy and active surveillance for treatment of prostate cancer. The rationale for focal therapy comes from its success in treating other malignancies. One of the challenges in applying such an approach to the treatment of prostate cancer has been the multifocal nature of the disease. This review addresses the selection of potentially ideal candidates for focal therapy and discusses which modalities are currently being used and proposed for focal therapy. Setting and meeting guidelines for oncologic efficacy is a challenge we must embrace to safely deliver this potentially revolutionary approach to treating men with prostate cancer.